Study of Uplink Interference in UMTS Network: ASIACELL Company, Iraq - Karim, Bakhtiar Ali; Rahaman Othman, Bzhar (Kurdistan Journal of Applied Research, 2020)
Universal Mobile Telecommunications System (UMTS), is the third generation (3G) of mobile communication which is based on the wideband code division multiple access (W-CDMA) radio access to provide bandwidth and spectral efficiency. Interference in 3G system is significantly lower compared to the preceded generations. However, it does not mean 3G is free from the issues associated with interferences, such as low signal quality and call drop. The interference level in UMTS can be measured by using the well-known parameter Received Total Wideband Power (RTWP). This parameter is affected by many factors such as number of the users connected to the system, combining second generation (2G) and 3G frequencies within the same geographical area, geographical causes (difference of Altitude), and hardware impairment. In this paper we intensively study how these factors affect the uplink interference level (i.e. RTWP value) in 3G system used by a particular telecommunications company, Asiacell company, Iraq. The obtained data shows that call drop is the most serious issue raised due to high value of RTWP in 3G system. We demonstrate that system enhancement, in terms of lower RTWP level, are obtained by adding second carrier to the sites, separating 2G band from 3G band using special filter, and optimizing the hardware components.